Circulating CD4+T/methylation signatures of network-oriented SOCS3, ITGAL, NFIC, NCOR2, PGK1 genes associate with hemodynamics in pulmonary arterial hypertension patients. (14th October 2021) - Benincasa, G; Maron, B A; Affinito, O; D'Alto, M; Franzese, M; Argiento, P; Schiano, C; Romeo, E; Bontempo, P; Golino, P; Berrino, L; Loscalzo, J; et al.
Abstract: Background: CD4+ T cells are associated with pulmonary arterial hypertension (PAH) pathogenesis but mechanistic insights are limited. Purpose: To identify differential CD4+ T methylation signatures in healthy controls vs PAH and evaluate a putative association with the cardiopulmonary hemodynamic profile of affected patients. Methods: We used RRBS platform to profile CD4+ T DNA methylome in the CLEOPAHTRA clinical trial. Results: Differentially methylated CpG sites (N=631) annotated to N=408 genes (DMGs). Most of them (65%) were hypermethylated and localized in distal intergenic (36%) and promoter regions (31%). Promoter-related network analysis established the PAH subnetwork highlighting 5 hub DMGs (SOCS3, GNAS, ITGAL, NCOR2, NFIC) and 5 non-hub DMGs (NR4A2, GRM2, PGK1, STMN1, LIMS2) as potential candidate genes (Figure 1). The Infinium Human MethylationEPIC BeadChip on CD4+ T cells from an independent study population confirmed the global RRBS-methylation trends. Both in idiopathic and Associated-PAH, each of these 10 network-oriented DMGs was strongly correlated with at least one hemodynamic parameter such as right atrial pressure (RAP), cardiac index (CI), mean pulmonary arterial pressure (mPAP), pulmonary vascular resistance (PVR), and pulmonary capillary wedge pressure (PCWP) (Figure 2). In addition, mRNA levels of the ITGAL, NFIC, NCOR2, PGK1 genes and the IL-6-STAT3-SOCS3 signaling axis were significantly upregulated in PBMCs from patients with PAH vs controls suggesting putative drug targets. Furthermore, both SOCS3 methylation and mRNA levels were positively correlated with cardiac index (CI) in idiopathic PAH whereas both PGK1 methylation and mRNA levels were positively correlated with RAP and inversely with CI in Associated PAH suggesting putative non-invasive biomarkers. Conclusions: This hypothesis-generating study shows for the first time that circulating CD4+ T methylation signatures, inclusive of SOCS3, ITGAL, NFIC, NCOR2, and PGK1 genes may yield insight into pro-inflammatory mechanisms that exacerbate vascular remodeling in PAH and suggest non-invasive biomarkers to optimize patient phenotyping and, possibly, prognostication in PAH. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): PRIN2017F8ZB89 from Italian Ministry of University and Research (MIUR) (PI Prof Napoli) and Ricerca Corrente (RC) 2019 from Italian Ministry of Health (PI Prof. Napoli).